Mapping the field of studies on social class and educational inequalities in Argentina - Meo, Analía Inés (Revista Enfoques Educacionales, 2017)
This paper maps the research on social class and educational inequalities at secondary level in Argentina. It offers a typology of studies according to their research problems, theoretical perspectives and methodology. It distinguishes four kinds of research traditions: the socio-structural, the socio-historical, the socioeducational and the identity and subjectivity turn. It is argued that, in the sub-field of Sociology of Education, there is coexistence of diverse and even antagonistic research traditions. Furthermore, this diversity could be understood both as a sign of the vitality of the field and of its low structuration and limitations. The vitality of the field is illustrated by the wide range of topics, questions, theories and methodsused by researchers since the 1980s. Among the indicators of the low structuration of Sociology of Education, the author identifies the persistence of theoretical 'silences’ and the marginality of reflexive accounts on how, who and what for knowledge is produced.